Visualisasi Interaksi Habitat Hewan dalam Lingkungan WebAR sebagai Media Pembelajaran Biologi - Atventitus Etwin Loho; Heny Pratiwi; Jundro Daud Hasiholan (Universitas Methodist Indonesia, 2025)
The study aimed to develop an interactive learning medium based on Web-based Augmented Reality (WebAR) markerless to visualize various animal habitats as part of Science education in elementary schools. The research employed the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The developed WebAR application allows students to explore 3D dioramas of animal habitats directly through a browser without additional installation. A beta test was conducted with 10 fifth-grade students from SDN 024 Samarinda using a Likert scale questionnaire that covered accessibility, visual display, interactivity, and user satisfaction. The test results showed an average score of 82.8%, indicating that the developed medium is well-received and effective in increasing students' motivation and concept understanding. This markerless WebAR medium provides a more immersive and contextual learning experience compared to conventional two-dimensional media. Future research could expand the number of respondents, test in different learning contexts, and add interactive features such as quizzes or narration to enhance learning engagement.